Implications of occupational locus and focus for public service motivation: Attitudes toward work motives across nations - Houston, David J. (2011)
Is occupational locus or focus important for public service motivation/ Does national context influence public service motivation? To answer both questions, the author examines attitudes toward work motives from national samples in 11 North American and Western European nations using multilevel binary logistic regression analysis. The findings demonstrate that the locus of an occupation in government and its focus on a public service activity both are important in shaping preferences for work motives related to public service motivation. Also the preference for work motives held by citizens is correlated with the type of welfare regime in a nation. Although it is less pronounced, some evidence suggests that the type of welfare regime influences preferences toward work motives among government employees. - Reproduced.
Keywords: Motivation